Terms questioned authentically by Hadith narrators in Sahih Bukhari and their semantic impact: A case study - Al-Jawfi, Hamda Bint Maqbool Bin Abdullah (Journal of Arts, 2023)
This study aims to investigate the terms questioned by Hadith narrators in Sahih Bukhari, and identify the subsequent impact on meaning understanding in light of examining some Hadiths on various aspects. The study is divided into four chapters. Chapter one dealt with the concept of authenticity questioning and its causes. Chapter two focused on authentically-questioned text terms with a doctrine semantic impact. Chapter three was concerned with authentically-questioned text terms with a jurisprudent perspective of meaning understanding. The fourth chapter discussed authentically-questioned Hadith text terms with regard to space and time dimension and the subsequent semantic impact. The study revealed that Hadith questioning may or may not have a doctrinaire or jurisprudential impact or making reference to a particular place and time. Hadith narrators addressed existing questioning just for accurate wording of the Prophetic tradition (Hadith), avoiding lie attributes to Prophet Mohammed peace be upon him. The study emphasized investigating and analyzing authenticity questioning in Hadith books and documents considering its significance in clarifying the meaning and identifying narrators’ accuracy in dealing with Prophetic Hadith to guarantee Islamic Sharia fabrication-free laws.